Menggali Makna dan Pentingnya Pembelajaran Sejarah Kebudayaan Islam Dalam Membangun Karakter Generasi Muda di Era Modern - Nur Asyifa Ananda; Noorazmah Hidayati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores the significance of Islamic cultural history education in shaping the character of the youth in the modern era. It emphasizes that Islamic cultural history is not merely a record of the past but a source of moral values that can guide individual character development. The research utilizes a literature review approach, collecting data from various sources, including journals and books, to highlight the relevance of historical lessons in contemporary life. Findings indicate that integrating innovative teaching methods and technology enhances student engagement and understanding. Furthermore, the study underscores the need for character education within the curriculum, promoting values such as tolerance, social responsibility, and ethical behavior. Ultimately, this article argues that a holistic approach to teaching Islamic cultural history can significantly contribute to the formation of a well-rounded, morally grounded generation capable of facing global challenges.